(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To assess the articles published on current treatments for Peyronie’s disease (PD) and it’s new development and to assist clinicians to select the effective management of PD by increasing understanding and awareness of the outcomes associated with current medical and surgical treatment options. Methods: A Hinari literature search was conducted to identify relevant, peer-reviewed, clinical and review articles published related to current treatment options and it’s new developments of Peyronie’s Disease. Search terms for this non-systematic review included ‘Peyronie’s disease’, ‘current treatment, outcomes’, new development. ‘Erectile dysfunction or ED’, search terms were searched separately and in combination. Case studies and editorials were excluded, primary manuscripts and reviews were included, and references of articles of interest were reviewed and key references were obtained. Result: Currently, there are several investigational minimally invasive and non-surgical treatment options for PD; however, surgical treatment remains the standard of care for patients with stable disease and disabling deformity or drug-resistant erectile dysfunction. Each of the different surgical procedures that are used for treatment of PD, including tunical shortening, tunical lengthening (plaque incisions or partial excision and grafting), and use of inflatable penile prostheses, carries its own advantages and disadvantages in terms of potential complications and postoperative satisfaction. No single, standard, surgical treatment for this disorder has prevailed and multiple variations of each type of procedure exist. Obtaining data on current treatment and its modifications to these procedures, and new surgical techniques and materials may serve to further guide Conclusion: The real etiology of Peyronie’s disease and the mechanisms of formation of the plaque still remain obscure. Although conservative management is obtaining a progressively larger consensus among the experts, surgical correction still remains the mainstay treatment for this condition. Treatment should be tailored to each patient after a detailed evaluation of disease severity and sexual function. Bangladesh Journal of Urology, Vol. 17, No. 2, July 2014 p.87-96